KAJIAN BENTUK BAHASA ISYARAT (PENGKODEAN) DALAM KOMUNIKASI ANAK USIA 3 TAHUN - Jaya Nasa Perta; Winda Azmi (Vokal: Jurnal Ilmiah Bahasa dan Sastra Indonesia, 2022)
The purpose of this study was to describe the form and solution of speech delay in children (using coding language) in communication. This research a descriptive method, with the type of qualitative research. The research was conducted by describing coded language as research data spoken by children as a form of communication. The source of the data in this study was in the form of a code from Raihana Yasmina (age 3 years 10 months). Data were collected by listening and free-to-talk techniques. The data analysis technique was carried out by interpreting the data to test the suitability of the coded language form with an analysis of the communication situation to find the speaker's intent. The findings of this study are, first, there are two forms of coding that are carried out by Raihana, namely by using body parts and using objects around them. Second, the solutions are expert therapy, traditional therapy, and speech habituation.